Case study of the promotion policy culture in the preservation of the dayak bidayuh nibakng religious tradition in the Borderlands Siding district, Bengkayang Regency - Yohanes, Yulius; Martinus, Martinus; Cosella, Messy; Wuysang, Julia Magdalena (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The Nibakng tradition is a vital cultural heritage that embodies local wisdom and is closely tied to the community's identity. However, with the rapid advancement of globalization and modernization, the tradition faces the risk of disappearing. This study aims to analyze cultural promotion policies and their role in preserving the Nibakng religious practice, which is embraced by the Dayak Bidayuh community in the border region of Siding District, Bengkayang Regency, West Kalimantan Province. A qualitative approach was employed, using in-depth interviews with local communities, traditional leaders, and policymakers, alongside document analysis of cultural promotion policies. The findings revealed that while these policies have contributed to the preservation of Nibakng, several obstacles remain, such as limited budget allocation, insufficient focus on involving younger generations, and challenges in local implementation. The study concludes that cultural promotion policies can help strengthen local cultural identity if they are supported by collaboration among local governments, traditional institutions, and communities. This research emphasizes the need for more comprehensive policy improvements, greater youth involvement, and enhanced cross-border cooperation with neighboring countries to ensure the sustainability of the Nibakng tradition, ultimately fortifying national identity in the border region.